Exploring the role of a participatory live music practice on nurses experienced levels of compassion satisfaction and fatigue: A mixed method study - Nina M. van den Berg; Wolter Paans; Barbara van Leeuwen; Maya J. Schroevers; Hanneke van der Wal – Huisman (PLoS ONE, 2026)
Objective To explore nurses’ compassion satisfaction and compassion fatigue in relation to a participatory live music practice, and to understand nurses’ own perspectives on this dynamic. Introduction A significant group of nurses experience compassion fatigue, the feelings of exhaustion and reduced capacity for empathy when caring for others, putting them at risk for work retention and turnover. Compassion satisfaction, the positive feelings derived from caregiving, may boost nurses’ well-being and resilience, and protects against compassion fatigue. Therefore, interventions enhancing compassion satisfaction provide dual benefits. This study examined to what extent an intervention based on participatory live music practice for nurses and their patients, by providing meaningful moments of compassion and bonding in the caring relationship, reduces nurses’ compassion fatigue and/or enhances their compassion satisfaction. Materials and methods A mixed-method explanatory design was applied. First, exploratory quantitative data in 30 nurses were obtained via surveys prior to and after a week of participatory live music practice. Compassion satisfaction and compassion fatigue were assessed using the 21-item Professional Quality of Life Scale (ProQoL). Secondly, sequential semi-structured interviews with 22 nurses were carried out in two phases. Quantitative data was analyzed using descriptive statistics and Wilcoxon Signed-Rank Test. Qualitative data underwent thematic analysis. Results Exploratory quantitative results suggested average levels of compassion satisfaction and fatigue, both before and after the week of participatory live music practice, with no significant changes over time. Qualitative results revealed two themes: (1) feelings of compassion satisfaction derived from observing patients’ response to the live music, leading to enhanced feelings of shared humanity and bonding, and a reconnection with nursing values; (2) perceived positive impact of the participatory live music on mood, work pleasure, and team dynamics. Conclusions While quantitative data showed no significant changes in levels of compassion fatigue and satisfaction in the period before and after the live music practice, qualitative data revealed that nurses perceive benefits and compassion satisfaction by engaging in a participatory live music practice in the hospital setting.